Atezolizumab-Related Sarcoidosis-Like Reaction in Early Breast Cancer Patient: Know It To Diagnose It: A Case Report with Review of the Literature - Tornincasa, Antonio; Canino, Fabio; Trudu, Lucia; Barbolini, Monica; Moscetti, Luca; Omarini, Claudia; Dominici, Massimo; Piacentini, Federico (Archives of Clinical and Medical Case Reports, 2022)
Here we report a case of sarcoidosis-like reaction in a patient while on neoadjuvant chemotherapy plus Atezolizumab for an operable HER2- positive breast cancer. The aim of the current article is to raise awareness about Atezolizumab-associated sarcoidosis, even in early breast cancer setting.